ON THE VALIDITY OF WEISSKOPF PHASE SHIFT IN THE PRESSURE BROADENING AND SHIFT OF SPECTRAL LINES (Biological Sciences - PJSIR, 2022)
The classical theory of collisional broadening and shift parameter (~, 8) of an isolated spectral line is used to obtainsimple analytical formulas for calculating both ~ and 8. These formulas are obtained on the assumption that the shortrange interaction is effective only in the broadening while the long range is effective in the shift of the spectral line. Theparameters ~ and 8 depend on the Weisskopfphase shift'll" = I. The obtained formulas are applied to both vandervaalsand Lennard - jones model potentials for some atomic pair interactions. The obtained results are in close agreement withthe numerical results obtained before. This verify the validity of both of the Weisskopf phase shift and the obtainedanalytical formulas.